Testing applications on the Web : test planning for mobile and Internet-based systems - Nguyen, Hung Quoc (Wiley Pub., 2003)
Testing software for Web and wireless applications comes with a unique set of issues. It is a complex process that requires testing code across servers, browsers, protocols and gateways. This guide presents the methods that are specific to testing Internet-based software.